Associations between obesogenic risk factors and depression among adolescents: a systematic review. Issue 1 (27th August 2013) - Hoare, E.; Skouteris, H.; Fuller‐Tyszkiewicz, M.; Millar, L.; Allender, S.
Summary Adolescence is a transitional life phase that is associated with heightened risk for two major health conditions – obesity and mental health problems. Given the established comorbidity of obesity and depression, one avenue that warrants further exploration is the association between obesogenic risk and obesity in the expression and maintenance of depressive symptoms. The aim of the current systematic review was to identify and evaluate the empirical literature reporting the relationships between obesogenic risk factors (physical activity, sedentary behaviour, diet and weight status) and depression in adolescents. A search of five databases for studies published over the last decade found 24 studies eligible for review. Relationships were found between lack of physical exercise, heightened sedentary behaviour, poor diet quality, obese or overweight and depression in adolescence. However, the finding that obesogenic risk factors are associated with poor adolescent mental health should be interpreted with caution as data typically come from non‐representative samples with less than optimal study design and methodology.